1994
DOI: 10.1115/1.2910220
|View full text |Cite
|
Sign up to set email alerts
|

Development of a k-ε Model for Bubbly Two-Phase Flow

Abstract: An extension of the k-ε model for bubbly two-phase flow is proposed and tested against experimental data. The basic assumption made is that the shear-induced turbulence and bubble-induced turbulence may be linearly superposed. This assumption results in a model with two time constants that matches both homogeneous two-phase turbulence data (Lance and Bataille, 1991) and pipe data (Serizawa, 1986). The coefficients of the single-phase k-ε model have not been modified and only one additional coefficient is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(61 citation statements)
references
References 0 publications
0
61
0
Order By: Relevance
“…These bubbles are involved in intense interactions with mean flow and turbulence, producing a complex two-phase bubbly flow field. It is well known that the presence of bubbles can suppress liquid phase turbulence (Wang et al, 1987;Kataoka and Serizawa, 1989;Serizawa and Kataoka, 1990;Lopez de Bertodano et al, 1994). Other studies have also revealed that bubbles may alter the local vorticity field and consequently deform or displace the vortex structure (Sridhar and Katz, 1999;Watanabe et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…These bubbles are involved in intense interactions with mean flow and turbulence, producing a complex two-phase bubbly flow field. It is well known that the presence of bubbles can suppress liquid phase turbulence (Wang et al, 1987;Kataoka and Serizawa, 1989;Serizawa and Kataoka, 1990;Lopez de Bertodano et al, 1994). Other studies have also revealed that bubbles may alter the local vorticity field and consequently deform or displace the vortex structure (Sridhar and Katz, 1999;Watanabe et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Many experimental and numerical studies involving the prediction of radial phase distribution in turbulent upward air-water flow in a pipe have appeared in the literature [61][62][63][64][65][66][67][68]. These studies indicated that the lateral forces that most strongly affect the void distribution are the lateral lift force and the turbulent stresses.…”
Section: Problem 1:turbulent Upward Bubbly Flow In a Pipementioning
confidence: 99%
“…For two-phase flow, several extensions of the k-ε model that are based on calculating the turbulent viscosity by solving the k and ε equations for the carrier or continuous phase only have been proposed in the literature [50][51][52][53][54][55]. In a recent article, Cokljat and Ivanov [49] presented a phase coupled k-ε turbulence model, intended for the cases where a non-dilute secondary phase is present, in which the k-ε transport equations for all phases are solved.…”
Section: The Governing Equationsmentioning
confidence: 99%
“…Nevertheless, from a practical point of view, second order modeling is still difficult to use and turbulence models based on turbulent viscosity concept, particularly two-equation models, remain widely used in industrial applications. Several two-equation models were developed for turbulent bubbly flows (Lopez de Bertodano et al, 1994;Lee et al, 1989;Morel, 1995;Troshko & Hassan, 2001). All of these models are founded on an extrapolation of single-phase turbulence models by introducing supplementary terms (source terms) in the transport equations of turbulent energy and dissipation rate.…”
Section: A) Turbulence Modelingmentioning
confidence: 99%